Physico-mathematical theory of high irreversible strains in metals - Greshnov, V. M. (Boca Raton, FL : CRC Press, 2019)
Presents a new physical and mathematical theory of irreversible deformations and ductile fracture of metals that acknowledges the continuous change in the structure of materials during deformation and the accumulation of deformation damage. Plastic deformation, viscous destruction, evolution of structure, creep processes, and long-term strength of metals and stress relaxation are described in the framework of a unified approach and model. The author then expands this into a mathematical model for determining the mechanical characteristics of quasi-samples of standard mechanical properties in deformed semi-finished products.
5.2. The defining equations of large cyclic deformation and deformation close to it6: Physico-phenomenological models of irreversible strains in metals; 6.1. Model of evolution of a microstructure under irreversible deformation of metals; 6.2. Kinetic physical-phenomenological model of dislocation creep, controlled by thermally activated slip of dislocations; 6.3. Kinetic physico-phenomenological model of long-term strength of metals; 6.3.1. General information about long-term strength; 6.3.2. Model of long-term strength. The general case of loading
OCLC-licensed vendor bibliographic record.
Keywords: Deformations (Mechanics) -- Mathematical models; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; SCIENCE / Solid State Physics; TECHNOLOGY / Material Science; TECHNOLOGY / Metallurgy